Pendekatan Kolaborasi Model Hexahelix dalam Pengelolaan Garam di Kabupaten Sumenep - Bayu Ardana; Singgih Manggalou (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze and map the roles of each stakeholder involved in hexahelix collaboration, focusing on salt management in Sumenep Regency. Data were collected through interviews, documentation, and observation as part of a descriptive qualitative research approach. The focus of the research is to identify stakeholders involved in hexahelix collaboration related to salt management in Sumenep Regency. The results of the study indicate that the hexahelix collaboration in salt management in Sumenep Regency has been running optimally. However, for salt management in Sumenep Regency to be successful, the hexahelix element as a whole needs to enhance its role. The government, academics, the business world, the media, and financial institutions form the hexahelix in salt management. Each part serves a specific purpose in achieving the common goal. While the implementation process is collaborative and complementary, it is important for all stakeholders to understand their primary functions before formulating policies and implementing the hexahelix initiative.